2017
DOI: 10.1093/tropej/fmx047
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Condition and Prevalence of Malaria Fever in Pakistani Children: Findings from a Community Health Survey

Abstract: SEC has a significant impact on the prevalence of malaria fever in the context of different regions in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…26 Wealth status of the households plays a key role in the health measures of the family. 27 Results of this study also demonstrate that the children of richest wealth quintile have more chances of full vaccination as compared with the poorest wealth quintile. It is also identified that as the wealth status of the family improves, the chance of child's complete vaccination coverage increases.…”
Section: Discussionsupporting
confidence: 51%
“…26 Wealth status of the households plays a key role in the health measures of the family. 27 Results of this study also demonstrate that the children of richest wealth quintile have more chances of full vaccination as compared with the poorest wealth quintile. It is also identified that as the wealth status of the family improves, the chance of child's complete vaccination coverage increases.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, we may conclude that the mother's better educational level might be considered a measure of protection against childhood undernutrition. Many studies have discussed the association between household socioeconomic status and child health, such as [7,33,39].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is considered to be a disease of the poor [ 45 – 47 ], and several studies have shown significant association between poverty and malaria [ 48 , 49 ]. There are also studies that have shown no significant association between malaria and SES of the household [ 17 , 50 52 ].…”
Section: Discussionmentioning
confidence: 99%